Hubungan Antara Kekhusyukan Shalat Dengan Kesejahteraan Subjektif Pada Santriwati Pondok Ta'mirul Islam Surakarta - Marret Nor Izzawati, Dewi, Setiyo Purwanto, S.Psi., M.Si, Dra. Darojat A., M.Ag (2016)
Being absorbed in praying (khusyuk shalat) become one of factors in the subjective welfare of the female students in the Islamic boarding school (pondok), because being absorbed in shalat makes an individual more patient and calm in facing problems, no much worried, and easy to thank God on all grace He gave. The female students who live in pondok are faced with many kinds of problems, so the comfort and peace influence the subjective welfare of the female students in order that the female students become individuals who are easy to thank God and get the subjective welfare. Therefore, the main objective of this research was to know the correlation between being absorbed in shalat and the subjective welfare in the female students of pondok pesantren (Islamic boarding school) Ta'mirul Islam Surakarta. The technique of sampling used was incidental sampling. The subjects used were as many as 100 people using the method of qualitative approach and the measurement of scale. The technique of analysis used was the Pearson product moment correlation. The results of data analysis obtained the coefficient of correlation rxy = -0.440 with significance = 0.000 p < 0.001, therefore, the hypothesis proposed was accepted, that it could be said that there was a very significant correlation between being absorbed in shalat and the subjective welfare of the female students of pondok Ta'mirul Islam Surakarta. The effecive contribution of being absorbed in shalat on the subjective welfare in the female students of Ta'mirul Islam was as much as 19.36% and the rest 80.64% was influence by other variables. Being absorbed in shalat has an empirical mean 124.08 and a hypothetical mean as much as 96 that were categorized as high. The subjective welfare had an empirical mean 82.52 and a hypothetical mean as much as 66 that were categorized as high.